Paulicéia literária:páginas e suplementos literários em jornais - Nunes, Monica de Fatima Rodrigues (2007)
This paper focuses on pages and literary supplements. It is a research that sought to locate, identify and characterize pages and literary supplements, inserted in Paulista newspapers for this study were: Correio Paulistanos, O Estado de S. Paulo, Diário Popular, Gazeta, Folha da Noite , Folha da Tarde, Diário de S. Paulo and Última Hora. Through a qualitative approach, we realized that the spaces for the arts and shows in the newspapers analyzed were given in different ways, not only in pages and literary supplements, such as the publication of daily sections of arts and shows, "without titles" footers of literary criticism ... (AU)